Knowledge of special nutrition for children with autism spectrum disorder among parents and special educators in Malaysia - Durratul Ain Shohaimi; Siti Farwizah Izzati Sahidan; Muhamad Afiq Zulkifly; Nabilah Tagor Hasibuan; Noor Akmal Shareela Ismail; Nur Hana Hamzaid; Nurul Izzaty Hassan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sufficient intake of macronutrients and micronutrients are essential for child growth. Many children with autism spectrum disorder (ASD) however are reported to be picky eaters which may lead to malnourishment. As diet and behaviour are importantly interconnected, this study aims to determine the level of knowledge on nutrition among parents and special educators of children with ASD. A cross-sectional study was conducted at a National Autism Centre in Kuala Lumpur, Malaysia from May to August 2018. A 37-item questionnaire was self-administered to the respondents who attended series of training of trainers’ sessions. The data was the collected and analysed descriptively. A total of 209 respondents participated with 153 parents and 56 special educators of children with ASD. Only 37.9% of the parents agreed that their children’s diet contain balanced nutrition. Majority of the parents and special educators had the perception that sugar, junk food and gluten are bad for the children but they were still given due to the accessibility and convenience. The low level of knowledge among parents and special educators about the nutrition of children with ASD indicates that a measure should be taken to increase the awareness and to overcome the malnutrition among ASD children.